2019
DOI: 10.5114/biolsport.2019.83506
|View full text |Cite
|
Sign up to set email alerts
|

Age-related influence on physical fitness and individual on-duty task performance of Portuguese male non-elite police officers

Abstract: (a) to analyse the effect of age on physical fitness (PF) and on-duty task (ODT) performance of male police officers (PO); (b) to analyse the relationship between PF and ODT performance of male PO; and (c) to identify the set of PF attributes which better predicts the ODT performance of male PO. A total of 97 Portuguese male non-elite PO (Public Security Police) took part in this cross-sectional study. Participants were allocated to four age categories (20-29, 30-39, 40-49, and >49 years old), and performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Maybe the specific physical activity that elite SPU agents are engaged on their daily police work life, but also their commitment to keep in shape as a professional duty, can explain these differences. This supposition is supported by the results presented by non-elite Portuguese police officers that show a clear age detrimental effect on this same somatic variables (Teixeira et al, 2019), namely a strong increase of relative fat mass (η 2 =0.357), and a small augmentation of their BMI (η 2 =0.153).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Maybe the specific physical activity that elite SPU agents are engaged on their daily police work life, but also their commitment to keep in shape as a professional duty, can explain these differences. This supposition is supported by the results presented by non-elite Portuguese police officers that show a clear age detrimental effect on this same somatic variables (Teixeira et al, 2019), namely a strong increase of relative fat mass (η 2 =0.357), and a small augmentation of their BMI (η 2 =0.153).…”
Section: Discussionsupporting
confidence: 55%
“…Relative to maximal strength, both right and left handgrip mean values of our sample were classified as above average from the general population (p50=50 kgf) (Dodds et al, 2014), but similar to the Portuguese non-elite Police officers (105.6 vs 106.6 kgf for the sum of both hands) (Teixeira et al, 2019). The bench press average value was close to the 90 th percentile of the general population reference values (ACSM, 2014a), and significantly better than the average Portuguese police officer within the same age range (93.0 vs 84.7; p<.001) (Teixeira et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As an important strategy to prevent a decline in the physical performance of police officers, Lagestad et al [16] proposed the need to provide opportunities for exercise during work, while Sörensen et al [17] reported that regular systematic training could help middle-aged police officers maintain physical fitness. Teixeira et al [9] reported that a regular strength and conditioning program, including power, core, and aerobic fitness, should be implemented for police officers to prevent a decline in performance and maintain physical capacity and occupational duties.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, Korean police officers undergo an annual physical fitness test; the records are stored and used as a reference for career promotion [8]. Additionally, the range of the interests of sports scientists has recently expanded to include tactical populations such as police officers [9]. These trends can be observed in reports by the National Strength and Conditioning Association (NSCA) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%